Research status of the effects of natural oligosaccharides on glucose metabolism. Issue 6 (27th November 2022) - Zhang, Minjiao; Chen, Yaobin; Chen, Ruoxin; Wen, Yuxi; Huang, Qihui; Liu, Yuanyuan; Zhao, Chao
Abstract: Diabetes is a common and frequently occurring endocrine and metabolic disease characterized by hyperglycemia with genetic tendency. At present, the drugs for diabetes include metformin, glimepiride, and acarbose. Although these drugs are effective, long‐term usage will produce secondary symptoms, such as Cushing's syndrome, limb hypertrophy, and even the risk of hypoglycemia. Many natural products have been found to treat diabetes, among which oligosaccharides are the most valuable. Oligosaccharides are low‐level oligosaccharides formed by the linkage of 2–10 monosaccharides through glycosidic bonds. Common oligosaccharides include chitosan oligosaccharides, xylooligosaccharides, konjac glucomannan, and brown algae oligosaccharides. It has the effects of reducing blood glucose, blood pressure, antioxidant, anti‐inflammatory, immune regulation, antiallergy, promoting the growth of bifidobacteria, and improving body health. With the continuous exploration of the medicinal value of natural oligosaccharides, more and more attention has been paid to their research. This review introduces some representative oligosaccharides with hypoglycemic effects, including their structural characteristics and hypoglycemic mechanism, as well as the application status and future development trend of oligosaccharides. Abstract : This review introduces some representative oligosaccharides with hypoglycemic effects, including their structural characteristics and hypoglycemic mechanism, as well as the application status and future development trend of oligosaccharides.